CONTRIBUTION ANALYSIS OF THE STATE DEFENSE AWARENESS PROGRAMME TOWARDS THE NATIONAL CHARACTER BUILDING - Adianto, Tri; Sulistiyanto, Sulistiyanto; Pudjiatmoko, Siswo; Ali, Yusuf (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
Globalization always lead to various kinds of influences, both negative nor positive, on the national character. In Indonesia, globalization has caused a significant degradation of national character which ended by the poor national character of the Indonesia’s young generation. In order to minimalize this impact, the Indonesian government has launched a program, named State Defense Awareness Programme (Program Pembinaan Kesadaran Bela Negara), in order to perform the mental revolution program and building the national character of Indonesia’s young generation, which has influenced by the negative effect of globalization. But until now, the Indonesian citizens are still not convinced that State Defense Awareness Programme can be an appropriate means in building the national character of Indonesian citizens. This condition was supported by the emergence of negative stigma related to State Defense Awareness Programme, which ultimately reduces the level of people participation in the program. This article was written by using a systematic approach and contribution analysis method. The results of this study are expected to be a consideration for the Indonesian government and citizens in implementing and joining this program. Based on the analysis result, it can be concluded that State Defense Awareness Programme has a significant contribution towards national character building of Indonesia’s young generation. A comprehensive and integrated implementation of this program will produce citizens or state defense cadres who has highly character of nationalism, patriotism, solidarity, skill, collaboration, discipline, leadership and so on, especially for Indonesians who are born and grow up on border areas or foreign country and have experienced a significant shift of state defense awareness. This program will also produce resilient, militant, and nationally awareness citizens based on the State Defense, Pancasila values and the 1945 Constitution norms.